A Study Of Chinese International Student Dropout: Acculturation Experiences And Challenges In A Pre-University English Language Improvement Program - Wang, Peiyu; Zhou, George (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2021)
With an increasing number of international students coming to Canada for higher education, Canadian universities are offering diverse English language improvement programs (ELIPs) to improve international students’ English proficiency. However, some Chinese international students struggle to pass such programs and eventually withdraw. This study examines the living and learning experiences of Chinese international students who dropped out of ELIPs and identifies the factors associated with their decisions to drop out. The findings indicate that Chinese international students dropped out due to academic failure that was related to low learning motivation, lack of time management and self-regulation, and insufficient academic and social integration. Implications for educators in higher education, study support services, and students are presented.